PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. JATIM JAYA PERKASA TERHADAP PENGELOLAAN KEBUN PLASMA (PERKEBUNAN MASYARAKAT) SAWIT BERDASARKAN PERJANJIAN KERJASAMA DENGAN KOPERASI UNIT DESA (KUD) BAGAN SIAPI-API DI KECAMATAN KUBU KABUPATEN ROKAN HILIR - Hazlan '; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
On the implementation of operations, capital investment companies are required to do a CSR or corporate social responsibility which in Pasal 74 ayat (1) Undang-Undang Perseroan Terbatas, Pasal 15 huruf (b) Undang-Undang Penanaman Modal, dan Pasal 1 angka 20 Peraturan Menteri Pertanian Nomor 98/Permentan/OT.140/9/2013 tentang Pedoman Izin Usaha Pertanian. In realizing the CSR company, PT. Jatim Jaya Perkasa plasma plantations into an agreement with KUD Bagan Siapi-Api. Initially the agreement done well, but the last few years PT. Jatim Jaya Perkasa reneged on the agreement or tort precisely Article 10 of the agreement. Based on these authors are interested in doing research with the title Responsibility PT. Against Jatim Jaya Perkasa Plasma Estate Management (Plantation Society) Oil Based Cooperation Agreement With Koperasi Unit Desa (KUD) Bagan Siapi-Api in Kecamatan Kubu Kabupaten Rokan Hilir.The author uses the theory of liability and the concept of corporate social responsibility. Sociological research type is descriptive. Location of the research conducted at the office of PT. Jatim Jaya Perkasa and Koperasi Unit Desa (KUD) Bagan Siapi-Api Rokan Hilir. With the sample population probalitity sampling techniques to obtain the desired results.The study was conducted at the office of KUD Bagan Siapi-Api in sub Kecamatan Kubu Bagan Siapi-Api Kabupaten Rokan Hilir, Kepenghuluan Teluk Nilap, egghead society Kubu and in the office of PT. Jatim Jaya Perkasa is located at Jalan Arifin Ahmad Pekanbaru 9. The study period from September 2015 until April, 2016.The result of this research is PT. Jatim Jaya Perkasa too many negotiations for the implementation of CSR and liabilities on the contents of the agreement when it was described in detail on the contents of the agreement. Furthermore, PT. Jatim Jaya Perkasa did indemnity payments unpaid plasma during the applicable agreements and prosecution to DRPD Rohil in order to take action against PT. Jatim Jaya Perkasa to comply with applicable laws, transparency related to the realization of CSR, renewal of licenses leasehold, and documents requiring Amdal waste management because it can damage the environment.Keywords: CSR-Plasma-Default